Sensory evaluation of a salami with extract of a colorant based on Ayrampo (Opuntia soehrensii) - Taramona-Ruiz, Luis (2024)
The objective of this study was to evaluate the elaboration of a salami that contains a natural colorant extracted from the seeds of ayrampo (Opuntia soehrensii), using an extract of this natural product at different concentration levels and using microbiological and sensorial characteristics as acceptance criteria of the final product. Initially, a physicochemical characterization of the seeds was carried out, which showed the high nutritional value of this natural product and its antioxidant power. In an experiment aimed at determining the effect of the concentration of the ayrampo seed extract on the quality of salami, it was shown that for extract concentrations between 150 and 250 g / L of water in the meat mass, there are no significant differences in terms of the characteristics of smell, color, taste and appearance of the final product. This was sensory tested through a 9-point hedonic scale and after statistical processing of the data, which included an analysis of variance carried out using the STATGRAPHICS Centurión XVI software. It was also confirmed, through microbiological tests supported by the NTS Nº 71/MINSA sanitary standard, that the final product is suitable for human consumption.